Peer Relationships and Indonesian Muslim Adolescents' Religiosity and Religious Coping: Selection and Influence. (24th July 2022) - Shen, Mengqian; DeLay, Dawn; Purwono, Urip; French, Doran C.
Abstract : The religious similarity of adolescents and their friends can arise from selection or influence. Prior studies were limited because of confounds that arose from the ethnic and religious heterogeneity of the samples and the use of cross‐sectional designs. SIENA was used in this two‐year longitudinal study of 825 Indonesian Muslim high school students (445 girls; mean age = 16.5 years) to assess peer selection and influence as these pertained to religiosity and religious coping. The analyses yielded significant influence but not selection effects for both religiosity and religious coping. This study is an important methodological advance over prior research and although limited by correlational data, nevertheless, provides evidence that adolescents influence their peers' religiousness.